Тадиційні сільські поселення Закарпаття - Федака, П. (Народна творчість та етнографія, 2008)
Specific features of the village settlings in Transcarpathia are described taking into account social, economical as well as historical factors. To the author’s mind, they kept their bright agricultural character, specific landscape and many elements of old settlings up to the end of the second half of the 20th century though they changed their appearance significantly.